The association of internet use and cognition among older adults: mediating roles of social networks and depressive symptoms - Zhu, Xiuyuan; Ni, Zihan; Zhu, Xiaoying; Yang, Yi; Xie, Shiyu; Wang, Xinguo; Yang, Xiaoguang (Frontiers in Psychiatry, 2025)
BackgroundTo explore the chain-mediated roles of social networks and depressive symptoms in the relationship between internet use and cognition among older adults.MethodsData were sourced from the 2018 China Longitudinal Aging Social Survey (CLASS). Structural equation modeling (SEM) was employed to analyze the potential mediating roles of social networks and depressive symptoms. Internet use, Lubben Social Network Scale (LSNS), the Center for Epidemiological Studies Depression Scale (CES-D) and Cognitive Scale were selected as indicators. Additionally, propensity score matching (PSM) was applied to further validate the robustness of the results by reducing potential selection bias and ensuring a more comparable distribution of observed covariates between internet users and non-users.ResultsOur analysis found that the use of the internet by older adults was positively correlated with their social networks (β=0.090, p<0.01). Both internet use and social networks exhibited negative associations with depressive symptoms in older adults respectively (β=-0.244, p<0.01; β=-0.136, p<0.01). Furthermore, both internet use (β=0.177, p<0.01) and social networks (β=0.032, p<0.01) positively predicted cognition in older adults, while depressive symptoms (β=-0.090, p<0.01) negatively impacted cognition. Moreover, our study showed that internet use not only directly influenced cognition of older adults but also indirectly impacted it through social networks and depressive symptoms, yielding a total mediated effect value of 0.026. Social networks and depressive symptoms accounted for 1.48% and 10.84% of the total effect respectively. Social networks and depressive symptoms served as chain mediators between internet use and cognition, constituting 0.49% of the total effect.ConclusionThis chain-mediated model provided a clear depiction of how social networks and depressive symptoms mediate the impact of internet use on the cognition of older adults. Enhancements in internet literacy and optimization of age-appropriate product designs are recommended to improve cognitive functions in older populations.